Comparison of cytotoxicity of Ag/ZnO and Ag@ZnO nanocomplexes to human umbilical vein endothelial cells in vitro. Issue 5 (13th December 2020) - Yan, Dejian; Xue, Zhiyong; Li, Shuang; Zhong, Cheng
Abstract: Novel metal and metal oxide‐based nanocomplexes are being developed due to their superior properties compared with nanoparticles (NPs) based on single composition. In this study, we synthesized Ag‐coated ZnO (Ag/ZnO) and Ag‐doped ZnO (Ag@ZnO) NPs. The cytotoxicity and mechanisms associated with the synthesized NPs were investigated to understand the influence of Ag positions on biocompatibility of the NPs. After exposure to human umbilical vein endothelial cells (HUVECs), Ag/ZnO, Ag@ZnO, and ZnO NPs all significantly induced cytotoxicity, but the cytotoxic effects of Ag/ZnO and Ag@ZnO NPs were more modest in comparison with ZnO NPs. At cytotoxic concentrations, all NPs significantly induced intracellular Zn ions, which suggested a role of excessive Zn ions on cytotoxicity of NPs. All types of NPs significantly induced the expression of endoplasmic reticulum (ER) stress genes including DNA damage‐inducible transcript 3 (DDIT3), X‐box binding protein 1 (XBP‐1), and ER to nucleus signaling 1 (ERN1), but Ag/ZnO and Ag@ZnO NPs were less effective to induce DDIT3 and XBP‐1 expression compared with ZnO NPs. Not surprisingly, only ZnO NPs significantly induced the expression of caspase 3. Combined, the results from this study showed that Ag/ZnO and Ag@ZnO NPs were less cytotoxic and less potent to induce ER stress gene expression compared with ZnO NPs, but there were no significant differences between Ag/ZnO and Ag@ZnO NPs. Our results may provide novel understanding about the biocompatibility of Ag–ZnO nanocomplexes. Abstract : This study synthesized Ag/ZnO, Ag@ZnO, and ZnO NPs and compared their toxicity to HUVECs. All types of NPs induced cytotoxicity, but ZnO NPs were more potent. At cytotoxic concentrations, all NPs significantly induced intracellular Zn ions. Ag/ZnO and Ag@ZnO NPs less effectively induced ER stress genes compared with ZnO NPs, and only ZnO NPs promoted caspase 3 expression. These results indicated that Ag positions in ZnO nanocomplexes were not important to influence their biocompatibility to HUVECs.